Alloy-free amorphous Pt–B–P/C electrocatalyst for enhanced methanol electro-oxidation - Poon, Kee Chun (2022)
This study reports the first known demonstration of amorphous Pt–B–P/C achieved via electroless reduction without the need for additional unstable transition metals. The amorphous structure was induced by simultaneous dual doping of both B and P by electroless reduction of Pt ion solution using a simple and facile process at ambient conditions. Amorphous Pt–B–P/C exhibited superior specific, mass activity compared to both commercial PtRu/C and crystalline Pt–B–P/C. Durability and CO poisoning resistance were also found to be better. XPS and annealing results suggest that synergistic effect of both doping and amorphous structure of Pt–B–P/C led to its overall enhanced catalytic performance.